The morphology strikes back - Sahm, Felix (Neuro-Oncology, 2024)
“Molecular trumps morphology” was the slogan for the WHO classification of Central Nervous System (CNS) tumors updated in 2016 (CNS4+) and is even more applicable for the current WHO classification (CNS5).1,2 As one of many implications, albeit certainly not the clinically most far-reaching, neuropathologists are asked whether they even need H&E sections anymore (which often is only a covert attempt to question the need for the neuropathologists themselves). On the contrary, how all these novel tests underlying the newly introduced biomarkers can be afforded in routine care is a pressing question, given the typically large equipment and reagent cost. In fact, these requirements have even been debated as incompatible with the goals and mandate of a World Health Organization guideline.3,4
Online veröffentlicht: 13. Juli 2024
Gesehen am 29.11.2024